Cost-effectiveness of two methods of screening for asymptomatic bacteriuria. - Rich, G (1976)
A comparison of two methods of screening schoolgirls for asymptomatic specimens of urine from 96.3, but that the home self-administered use of dipslides was successful in only 70.2%. The failure to obtain the return of satisfactory dipslides was most frequent in children under seven and over 11 years of age, and in children from the lower social classes; satisfactory dipslides were returned by 84% of children from social classes I, II, and III non-manual workers, but by only 58% of children from social class V and the unemployed. The cost per child screened was pounds 0.77 with the supervised method and pounds 0.26 with the dipslide method. An alternative supervised method which would have successfully screened 85% would have cost pound 0.55 per child screened. Using the home dipslide method, the cost per case of asymptomatic bacteriuria detected would vary from pounds 10.40 to pounds 20.00, depending on the age group screened.